1969
DOI: 10.1007/bf02391667
|View full text |Cite
|
Sign up to set email alerts
|

Spin-forbidden resonance multiplets in light elements

Abstract: Abstract. We present new laboratory data on the multiplets 2s z IS --2s2p aP, 2s22p 21, _ 2s2p2 4p, and 2s22p 2 zP --2s2p z "5S in nitrogen, oxygen and fluorine, and discuss the Z-dependence of their wave-numbers. These multiplets are very faint in laboratory light sources, but can become prominent in astrophysical sources of low density. Our results confirm the solar identifications of the nitrogen and oxygen multiplets made by Burton et al. Predicted positions of the corresponding multiplets in neon are give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0

Year Published

1970
1970
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 7 publications
5
20
0
Order By: Relevance
“…Results are compared with extrapolated values from observed data. For B I our estimate of the excitation energy 28 959 ± 5 cm −1 is in better agreement with the values obtained by Edlén et al (1969) than those reported by Kramida and Ryabtsev (2007). Our method is validated by applying the same procedure to the separation of these levels in C II.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Results are compared with extrapolated values from observed data. For B I our estimate of the excitation energy 28 959 ± 5 cm −1 is in better agreement with the values obtained by Edlén et al (1969) than those reported by Kramida and Ryabtsev (2007). Our method is validated by applying the same procedure to the separation of these levels in C II.…”
supporting
confidence: 85%
“…In generating the configuration interaction matrix we used the Breit-Pauli Hamiltonian but with only the relativistic shift operators, because of the size of the expansion and the small effect from the J -dependent terms. Tables II-IV Edlén et al [1] 28866 ± 15 Kramida and Ryabstev [2] 28643.1 ± 1.8…”
Section: The C Ii Quartet-doublet Energy Separationmentioning
confidence: 98%
See 1 more Smart Citation
“…They report EA's of 268.6(17) and 273.2(2) meV, respectively, as the result of an initial valence correlation MCHF calculation that neglects core polarization effects. Sundholm and Olsen estimate core-valence correlations to lower the EA to 267.8 (20) meV, whereas Froese Fischer et al predict the EA to increase to 279.5 (20) meV through the inclusion of core-valence and core-core correlations (the latter via core rearrangement). However, the experimental EA of 277(10) meV [11] agrees with all of the above values within uncertainties; hence the fundamental question as to the effect and strength of core-valence and core-core correlations in B 2 remains open and controversial.…”
mentioning
confidence: 98%
“…In the same paper he confirms the identification of A4412 as Arxiv and of X 55334 as Arx, by a study of the Z-dependence of the z p intervals of the configurations 2s 2 2p and 2s 2 2p 5 . Edlen et al have also published a paper entitled 'Spin-Forbidden Resonance Multiplets in Light Elements' (18).…”
Section: Vacuum Uv Atomic Spectramentioning
confidence: 99%